Knowledge and attitudes of secondary and higher secondary school teachers toward mental illness in Ahmedabad - Nimesh Parikh; Minakshi Parikh; Ganpat Vankar; Chintan Solanki; Girish Banwari; Prateek Sharma (Indian Journal of Social Psychiatry, 2016)
Background: Teachers can be trained in early identification of possible mental illness and referral which is well-established in the west and lacking in India. Hence, we attempt to study the knowledge and attitudes of secondary school teachers toward mental illness and probable gender differences in these measures. Materials and Methods: Five hundred and twenty teachers from English medium schools of Ahmedabad city were assessed by a self-reported, predesigned and pretested 25 item questionnaire, the first 15 of which assessed their knowledge about mental illnesses and the remaining 10 pertained to negative attitudes. Results: 79.4% of teachers were 45 years or less, 77.5% were female teachers and 86.9% were married. 76% of teachers scored <7 out of 15 which points toward majority of them having inadequate knowledge. 63.6% scored 5 or more on the negative attitudes questionnaire, which points toward high prevalence of negative attitudes. Females had comparatively more knowledge than males about symptoms and management of mental illness, although there was no significant gender difference in the attitude toward mental illnesses. Conclusion: The knowledge of teachers about mental illness is insufficient, and they hold a lot of stigma against mentally ill as demonstrated by their low score in attitude.